Structural bond behaviour of ribbed GFRP rebars in concrete beams under dynamic loading - Mukalay, J. N. (Vaal University of Technology, 2019)
This research investigated the structural bond strength of GFRP rebars in concrete beams under dynamic loading with the aim to characterize the structural bond behaviour and evaluate the limitations of the GFRP rebars under dynamic loading. The dynamic loading in this study was set at 500 repeating cycles to simulate a more realistic dynamic loading scenario such as earthquake since most dynamic loading studies are carried under ten repeating cycles. The experimental work was divided into 2 main tests which were firstly, the tensile tests of the GFRP rebars in order to evaluate the tensile strength of the rebars and characterize their properties. Secondly, the flexural tests of GFRP and steel reinforced concrete beams in order to evaluate the bond strength of GFRP and steel rebars, to characterize the average bond strength of GFRP and steel reinforced concrete beams under dynamic loading and finally to compare the average bond strength of GFRP rebars to Steel rebars in both dynamic and static loadings. The tensile tests were carried out using a Universal Testing Machine (UTM) and the results of the tensile tests of the GFRP rebars showed that the average experimental tensile strength of GFRP rebars was only 56.65% of the nominal tensile strength provided on the supplier data sheet. As for flexural tests, they were carried out through a four-point bending test using a UTM in conjunction with a universal dynamic shaker to create the dynamic loading set up. Steel reinforced concrete beams were used as control beams during the tests and factors such as the tensile strength of the GFRP rebars, the slip of the rebars, the load-deflection relationship and the stress-strain relationship were investigated. The results of the tests showed that the tensile strength of the GFRP rebar is strongly proportional to the maximum beam load bearing capacity and the maximum stresses of GFRP reinforced concrete beams. The results also showed that the average bond strength of GFRP rebars in static loading (8.44 MPa) was only 80% of the average bond strength in dynamic loading (10.95 MPa). Moreover, the experimental work showed that the failure of GFRP reinforced concrete beams depicted large deflections (19 mm) and slips (5 mm to 12.5 mm) when compared to steel reinforced concrete beams (for which the maximum deflection was 9.66 mm at failure and slippage values of 2 mm to 10 mm). Based on that it could be stipulated that the tensile strength of GFRP rebars is one determinant factor to the bond strength behaviour of GFRP rebars in concrete. Hence, the structural bond behaviour of GFRP rebars could be well-defined if more studies were done on the bond behaviour of GFRP rebars in concrete beams under dynamic loading using another type of GFRP rebars that would consist of a relatively high tensile strength as compared to the ones used in this study and different surface texture.
M.Tech. (Department of Civil Engineering, Faculty of Engineering and Technology), Vaal University of Technology
Keywords: Ribbed GFRP rebars; Reinforced concrete; Universal Testing Machine (UTM); Structural bond strength; Steel rebars; Dissertations, Academic -- South Africa; Reinforced concrete; Concrete beams -- Testing